Cognitive and hedonic responses to meal ingestion correlate with changes in circulating metabolites. Issue 12 (7th June 2016) - Malagelada, C.; Barba, I.; Accarino, A.; Molne, L.; Mendez, S.; Campos, E.; Gonzalez, A.; Alonso‐Cotoner, C.; Santos, J.; Malagelada, J.‐R.; Azpiroz, F.
Abstract: Background: We have previously shown that meal ingestion induces cognitive perception (sensations) with a hedonic dimension (well‐being) that depends on the characteristics of the meal and the appropriateness of the digestive response. The aim of the present study is to identify metabolomic biomarkers of the cognitive response to meal ingestion. Methods: In 18 healthy subjects, the response to a test meal (Edanec, 1 kcal/mL) ingested until maximum satiation (50 mL/min) was assessed. Perception measurements and blood samples were taken before, at the end of the meal, and 20 min after ingestion. The cognitive response and the hedonic dimension were measured on 10 cm scales. Metabolomic analysis was performed using nuclear magnetic resonance (NMR) spectroscopy and values of triglycerides, insulin, peptide YY (PYY), and glucagon‐like peptide‐1 (GLP‐1) were determined using conventional laboratory techniques. Key Results: Ingestion up to maximum satiation induced sensation of fullness and decreased digestive well‐being. The total amount ingested by each subject correlated with the basal sensation of hunger, but not with other sensations or blood metabolite levels. Immediately after ingestion, satiation correlated with an increase in glucose ( R = 0.49; p = 0.038) and valine levels ( R = 0.48; p = 0.043). Twenty‐minutes after finalizing ingestion, triglyceride levels had significantly increased which correlated with the recovery in well‐being ( R = 0.48; p = 0.046) and the decrease in desire to eat a food of choice ( R = −0.56; p = 0.016). The increase in lipids inversely correlated with abdominal discomfort ( R = −0.51; p = 0.032). Conclusions & Inferences: Cognitive and hedonic responses to meal ingestion correlate with changes in circulating metabolites, which may serve as objective biomarkers of perception. Abstract : Meal ingestion induces cognitive responses, such as satiation and fullness, with a hedonic dimension (digestive well‐being and satisfaction). Both cognitive and hedonic responses correlated with changes in specific metabolites during the postprandial period.